Modelling knowledge based systems using the executable modelling framework (XMF) - Abdullah, Mohd Syazwan; Evans, Andy; Benest, Ian; Paige, Richard; Kimble, Chris (2004)
There is no standardised approach to modelling knowledge-based systems; where modelling is adopted, the techniques used are those from the software engineering domain.These tend to be used in an ad hoc way and are highly dependent on the experience of the knowledge engineers.This paper presents the adoption of a profile mechanism for the design of knowledge-based systems.The profile is created using the meta-model extension approach of UML and is based on XMF (executable Meta-modelling Framework).XMF is an extension to the existing standards for meta-models: MOFT OCL and QVT. XMF offers an alternative approach in profile design which allows modification or the addition of new modelling constructs that are easily integrated with the core meta-model of UML